Questions of management of patients with hard-to-treat remitting multiple sclerosis - E. V. Popova; M. V. Melnikov; A. N. Boiko; V. V. Murugin; M. V. Paschenkov (Медицинский совет, 2015)
82 patients diagnosed with remitting multiple sclerosis, (MS) undergoing treatment with fingolimod were followed up for minimum 12 months at the Moscow Multiple Sclerosis Centre. The purpose of the follow-up was to evaluate the effects of fingolimod. 9 of 12 patients were subject to a comprehensive immunological examination to identify subpopulations of circulating T-cells. All patients were in clinical remission at the time of recruitment. All patients showed a significant decrease in the frequency of exacerbations during therapy with fingolimod. The disability status on the EDSS scale did not progress during the whole year of the follow-up. The therapy showed significant decrease in the production of IL-17 and the amount of TH17 cells in comparison with the control group, thus demonstrating a relevant decrease in the the autoimmune process activity. Withdrawal of fingolimod in 6-8 weeks was associated with normalization of the lymphocyte level in the peripheral blood due to drug elimination and wash-out of S1P receptors. However, given that wash-out of S1P receptors results in increased production of IL-17 and, consequently, higher BBB permeability, it is appropriate to name the disease reactivation as "rebound syndrome" which is primarily associated with a sharp increase in IL-17. This raises questions about management of patients who for various reasons need withdrawal of fingolimod therapy.